PERILAKU MAKAN GAJAH SUMATERA (Elephas maximus sumatranus Temminck.) TIM FLYING SQUAD DI TAMAN NASIONAL TESSO NILO (TNTN) - Ofrinaldi '; Defri Yoza; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The sumatran elephants including herbivorous animals that require the availability of sufficient food forage habitat. The sumatran elephants also need vegetated habitat trees for supplementary food to meet the needs of the mineral calcium to strengthen bones, teeth, and tusks. Digestion is not perfect, elephants need food very much is 200-300 kg of biomass per day for each adult elephants or 5-10% of their body weight. Elephants eating behavior is very dominant behaviors performed of Sumatran elephants. The percentage difference eat elephant behavior likely influenced by body weight, gender, age, differences in habitat area, number and type of feed available. The sumatran elephants uses their trunks to pick up food, starting from choosing foods perceived with its trunk up food withdrawn or revoked then cleaned with a wave of food into the body of the elephants when it is completely clean of dirt, the elephant will start to eat the food with his mouth.Type of food usually eaten for at pasture in nature include: young leaves of various herbaceous plants wild roots and liana, young rattan and shoots rattan, bark of tree species at a sampling rate, bamboo shoots and young thorns, grass reed and all parts of wild banana. Keywords: Behavior, Sumatran elephants, Tesso Nilo National Park